Study of the Properties of Au/Ag Core/Shell Nanoparticles and its Application - Mohammadi Bilankohi, Sara; Ebrahimzadeh, Majid; Ghaffary, Tooraj (Indian journal of science and technology, 2015)
Light absorption and scattering by nanoparticles has interesting history in physics and one of basic problems of advanced electrodynamics and it is an interesting subject for which Mie theory was developed long ago. In this article, the authors report the optical extinction, absorption and scattering properties of Au and Au/Ag nanoparticles. These nanoparticles can be applied as coating materials. Results showed that optical properties of Au/Ag core/shell nanoparticles are highly dependent on many factors such as size, index of environment, intrinsic properties, and surface chemistry. Also, when Au nanoparticles diameter is kept constant at 10 nm, the spectrum has a peak at visible area. If the shell thickness is increased, the peaks arise to the high and become more intense. Thinning the silver shell layer has a high increase in polarization at the sphere boundary, which yields the more intense extinction peaks. They expect that the Au/Ag nanospheres can be used in nanophotonics industry based on the near-field, optical devices, medical and solar energy.